Prunning technique and foliar fertilizer application to improve yield of pecco in fourth prunning year of tea plant - haq, muthia syafika; Mastur, Adhi Irianto; Karyudi, Dr H (Jurnal Penelitian Teh dan Kina, 2016)
Effect of prunning technique and foliar fertilizer application had been conducted to improve yield of pecco in the Research Institute for Tea and Cinchona experiment station, Gambung, Indonesia with altitude of 1.350 m above sea level, and with andysol soil type. The experiment was held from July to October 2015 in tea production field area containing 480 plants. The clone was GMB 7and was in the fourth prunning year, interval of plucking pecco was seven days. The experiment was arranged in a randomized block design with four treatments, replicated six times. Foliar fertilizer application was performed following every plucking. The results indicated that breaking apical dominance of tea short by 5 cmâ10 cm of prunning above plucking table combined with foliar fertilizer application of N 1% and ZnSo4 2% + 0,1% of humic acid, could increase weight of pecco per plot in the first nine weeks of the prunning. This treatment was better than the other three. But the percentage of pecco shoots was low, lower than 50%, the weight of one pecco was also very low 0,7 g, indicating that the treatment of harvesting pecco in the fourth prunning year was not recomended to be practiced in improving yield of pecco.